Quartz Crystal Microbalance With Dissipation Monitoring: A Versatile Tool to Monitor Phase Transitions in Biomimetic Membranes - Neupane, Shova; De Smet, Yana; Renner, Frank U.; Losada-Pérez, Patricia (Frontiers in Materials, 2018)
Solid-supported lipid membranes are popular models that connect biological and artificial materials used in bio-technological applications. Controlling the lipid organization and the related functions of these model systems entails understanding and characterizing their phase behavior. Quartz crystal microbalance with dissipation (QCM-D) is an acoustic-based surface-sensitive technique which is widely used in bio-interfacial science of solid-supported lipid membranes. Its sensitivity to mass and energy dissipation changes at the solid-lipid layer-liquid interface allows the detection of phase transformations of solid-supported membrane geometries. In this perspective, we highlight this valuable feature and its related methodology, review current advances and briefly discuss future perspectives. Furthermore, a specific example on the ability of QCM D to detect lipid organization changes of cholesterol containing solid-supported lipid vesicle layers (SVLs) upon the addition of aspirin is also provided